cálculo da equação 5(x+1) +6(x+2) =9(×+3)
Soluções para a tarefa
Respondido por
1
Aplicar a distributiva
5.(x+1) + 6.(x+2) =9.(x+3)
5x + 5 + 6x + 12 = 9x + 27
5x + 6x + 5 + 12 = 9x + 27
11x + 17 = 9x + 27
11x - 9x = 27 - 17
2x = 10
x = 10/2
x = 5
Resposta: 5
5.(x+1) + 6.(x+2) =9.(x+3)
5x + 5 + 6x + 12 = 9x + 27
5x + 6x + 5 + 12 = 9x + 27
11x + 17 = 9x + 27
11x - 9x = 27 - 17
2x = 10
x = 10/2
x = 5
Resposta: 5
Respondido por
1
1º passo
5x + 5 + 6x +12 = 9x + 27
2º passo
5x +6x -9x = 27 -5 -12
3º passo
2x = 10
4º passo
x= 10/2
x= 5
5x + 5 + 6x +12 = 9x + 27
2º passo
5x +6x -9x = 27 -5 -12
3º passo
2x = 10
4º passo
x= 10/2
x= 5
Perguntas interessantes
Geografia,
11 meses atrás
Física,
11 meses atrás
História,
11 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás